Assessment of the German Version of Brief Assessment of Cognition in Schizophrenia (BACS) - Matin Mortazavi; Jakob Amon; Iris Jäger; Genc Hasanaj; Zahra Aminifarsani; Kristin Fischer; Matthias Gamer; Alkomiet Hasan; Richard S.E. Keefe; Gabriele Sachs; Peter Falkai; Daniel Keeser; et al. (Schizophrenia Research: Cognition)
Background: Cognitive impairments are a hallmark of schizophrenia-spectrum disorders (SSD), contributing to poor treatment outcomes and a key treatment target. The Brief Assessment of Cognition in Schizophrenia (BACS) battery is a validated tool designed to evaluate affected core domains in SSD. The present study evaluated psychometric properties of the German version of the BACS in a representative sample of individuals with SSD and healthy control subjects. Methods: N = 107 individuals with SSD and n = 175 healthy controls were assessed with the German version of the BACS. Diagnosis was confirmed with the Mini International Neuropsychiatric Interview according to DSM-V. Validity was assessed through pair-wise comparisons between SSD individuals and healthy controls and by using receiver operating characteristic analysis. Internal consistency as a measure of reliability was evaluated using McDonald's Omega and Cronbach's Alpha in addition to factor and principal component analysis. Results: All individuals with SSD exhibited significantly lower z-scores across all BACS subtests and BACS composite scores (Z < -1.5) compared to healthy controls. ROC analysis revealed good diagnostic accuracy with an AUC of 0.83 (95%CI: 0.78,0.88, sensitivity = 0.75, specificity = 0.75). Similar results were observed in sub-cohorts comprising clinically stable SSD patients and those with younger ages (18–35 years old). A unidimensional structure, supported by McDonald's Omega (ω = 0.72) and principal component analysis, confirmed robust internal reliability. Conclusions: The German BACS demonstrates strong validity and internal reliability when assessed in a representative case-control sample. This study provides an extensive normative dataset for individuals with SSD in German-speaking populations, facilitating future research and clinical assessments of cognition.